The Influence of Green Human Resource Management and Job Training on Employee Work Productivity with Work Motivation as a Mediating Variable at PT Astronacci International - Sirait, Mila Oktavia; Sitompul, Grace Orlyn; Sinaga, Judith Tagal Gallena (Institut Teknologi dan Bisnis Asia Malang, 2025)
This study investigates the influence of Green Human Resource Management and job training on employee work productivity, with work motivation as a mediating variable. The sampling technique was based on Cohen’s table, and from a population of 107, a total of 82 respondents were selected according to the table's provisions. To test the hypotheses, the Partial Least Squares (PLS) method was employed in this research. The results show that Green Human Resource Management has a positive and significant contribution to increasing employee work motivation. Moreover, it also has a significant and positive effect on employee work productivity. Work motivation, in turn, has a positive and significant influence on employee work productivity. On the other hand, job training was found to have a positive and significant effect on enhancing work motivation, but no significant effect on employee work productivity. Green Human Resource Management has a positive and significant influence on employee work productivity through work motivation, and job training also has a positive and significant influence on employee work productivity through work motivation